2023
DOI: 10.1029/2023jd038921
|View full text |Cite
|
Sign up to set email alerts
|

First Online Observation of Aerosol Total Organic Nitrogen at an Urban Site: Insights Into the Emission Sources and Formation Pathways of Nitrogenous Organic Aerosols

Xu Yu,
Min Zhou,
Jinjian Li
et al.

Abstract: Nitrogen (N) is a constituent element of ambient organic aerosol; however, we have limited knowledge of the total quantity of organic N (ON) and its relative importance to aerosol N due to a lack of effective analytical methods for ON. Here, we report first online measurements of ON in particulate matter (PM2.5) in urban Shanghai in summer of 2021 using a newly developed aerosol nitrogen analyzer. ON accounted for an average of 25% of total aerosol N and varied in the range of 5%–64% on the hourly scale. Hourl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…The detection of its existence within aerosols serves as a reliable indicator of emissions resulting from either biomass burning or even biogenic salt particles 39 thereby facilitating the identification and understanding of their origins. Other studies have demonstrated that their analysis, encompassing concurrent measurements of pollutants indicative of sources 40 and samples of cloudwater, 41 has contributed to a broader understanding of the factors contributing to elevated levels of organic nitrates in the atmosphere. The carbonaceous component is a substantial element of particulate matter in the atmosphere, frequently comprising 20−50% of the total aerosol mass.…”
Section: Resultsmentioning
confidence: 99%
“…The detection of its existence within aerosols serves as a reliable indicator of emissions resulting from either biomass burning or even biogenic salt particles 39 thereby facilitating the identification and understanding of their origins. Other studies have demonstrated that their analysis, encompassing concurrent measurements of pollutants indicative of sources 40 and samples of cloudwater, 41 has contributed to a broader understanding of the factors contributing to elevated levels of organic nitrates in the atmosphere. The carbonaceous component is a substantial element of particulate matter in the atmosphere, frequently comprising 20−50% of the total aerosol mass.…”
Section: Resultsmentioning
confidence: 99%
“…CHON compounds are key players in the atmospheric nitrogen oxide cycle, contributing significantly to reactive nitrogen budgets . They are abundant in the atmosphere of large cities, often originating from sources such as biomass burning, vehicle emissions, and both day and night-time chemical processes . Nitrogen-containing organic compounds, including nitro-aromatics, are crucial in forming atmospheric brown carbon and profoundly affect its light-absorbing properties. , A substantial portion of these nitrogen-containing organics originate from secondary formation process in which gas-phase precursors are oxidized .…”
Section: Introductionmentioning
confidence: 99%